2011
DOI: 10.2174/138161211798764942
|View full text |Cite
|
Sign up to set email alerts
|

Females Live Longer than Males: Role of Oxidative Stress

Abstract: One of the most significant achievements of the twentieth century is the increase in human lifespan. In any period studied, females live longer than males. We showed that mitochondrial oxidative stress is higher in males than females and that the higher levels of estrogens in females protect them against ageing, by up-regulating the expression of antioxidant, longevity-related genes. The chemical structure of estradiol confers antioxidant properties to the molecule. However, the low concentration of estrogens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
89
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(93 citation statements)
references
References 0 publications
4
89
0
Order By: Relevance
“…The present work highlights the relevance of using mitochondrial-isolated fractions from male and female rats, which is very rare in the literature. Although we did not observe basal differences in mitochondrial preparations from both genders in most of the parameters investigated, except when measuring maximal respiration due to freezing/thawing cycles, it is known that estrogens have protective effects, enhancing antioxidant defenses and decreasing mitochondrial dysfunction (Borras et al, 2007;Eskes and Haanen, 2007;Vina et al, 2011). For instance, in liver mitochondrial the H 2 O 2 levels are lower in females than in males (Fig.…”
Section: Discussionmentioning
confidence: 65%
“…The present work highlights the relevance of using mitochondrial-isolated fractions from male and female rats, which is very rare in the literature. Although we did not observe basal differences in mitochondrial preparations from both genders in most of the parameters investigated, except when measuring maximal respiration due to freezing/thawing cycles, it is known that estrogens have protective effects, enhancing antioxidant defenses and decreasing mitochondrial dysfunction (Borras et al, 2007;Eskes and Haanen, 2007;Vina et al, 2011). For instance, in liver mitochondrial the H 2 O 2 levels are lower in females than in males (Fig.…”
Section: Discussionmentioning
confidence: 65%
“…Errors in genes encoding inflammatory or anti‐inflammatory molecules are candidates for increasing risk of developing complications from coronary artery disease 36. There are sex‐specific variations in NF‐κB activity, which may play a role in development of CED and atherosclerosis 37, 38…”
Section: Discussionmentioning
confidence: 99%
“…Aging studies are mainly focused on gender-related differences in life span [10,[17][18][19][20]. Numerous studies have reported that females live significantly longer than males both in mammals and other vertebrates, as well as in some invertebrate species [18,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have reported that females live significantly longer than males both in mammals and other vertebrates, as well as in some invertebrate species [18,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%